A rare case of toxic epidermal necrolysis in pregnancy - Yadav, Reena; Srivastava, Astha; Pawar, Preeti; Mendiratta, Vibhu; Tayal, Prerna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Stevens-Johnson syndrome (SJS) is a group of toxic necrolytic group of disorder of skin and mucous membrane with significant morbidity and mortality. It is a highly serious allergic reaction to medications affecting the skin and mucous membranes. Pregnant women with SJS or toxic epidermal necrolysis (TEN) are a unique subset, and both conditions can simultaneously affect the mother and fetus. It is a rare condition with a reported incidence of one case per million people per year. Till date, few cases of pregnancy with SJS/TEN have been reported. We are reporting a case of 20-year-old primigravida with 31+3 weeks of gestation presenting with extensive toxic epidermal necrosis. Attack of SJS developing in pregnancy can be fatal because immunity is compromised. This patient was managed in our institute with involvement of multidisciplinary team and had a successful pregnancy outcome. Perinatal outcome was also good in this case.